Back pain and its risk factors in Brazilian adolescents: a longitudinal study. Issue 1 (February 2021) - Noll, Matias; Candotti, Cláudia Tarragô; Rosa, Bruna Nichele da; Vieira, Adriane; Loss, Jefferson Fagundes
Owing to the lack of longitudinal studies in Latin American countries, we aimed to evaluate back pain and its risk factors in a 3-year longitudinal study of Brazilian adolescents. We analysed data of 525 adolescents (aged 11–16 years) attending primary school (fifth to eighth grade) in Brazil. The students were administered the self-reported Back Pain and Body Posture Evaluation Instrument (BackPEI) questionnaire in 2011 and at a follow-up evaluation that was conducted 3 years later (2014). Back pain was the outcome variable; the exposure variables included exercise, behavioural, hereditary and postural factors. Generalized estimating equations were used to perform a Poisson regression model with robust variance to evaluate the risk factors for back pain. The prevalence of back pain at baseline was 56% ( n  = 294); this increased significantly at the 3-year follow-up evaluation to 65.9% ( n  = 346). The frequency of experiencing back pain also significantly increased after 3 years in both boys ( p  = 0.002) and girls ( p  = 0.001). The prevalence of back pain increased significantly in adolescents up to the age of 13 years, stabilized in those aged 14 years and older and was higher among girls. A family history of back pain (in the parents), watching television for lengthy periods and carrying a backpack asymmetrically were predictors for back pain.